Recent changes in the pharmacovigilance system in the Russian Federation and the EAEU - G. N. Gildeeva; A. V. Belostotsky (IRBIS LLC, 2019)
The Eurasian Economic Union (EAEU) is an international organization for regional economic integration, established by the Treaty on the Eurasian Economic Union, which currently includes 5 countries - Russia, Kazakhstan, Belarus, Armenia and Kyrgyzstan. The EAEU ensures the freedom of goods movement, as well as services, capital and labor, conducting a coordinated, agreed/unified economic policy. The current practice of pharmacovigilance in the EAEU is of interest to potential foreign investors and market players.The aim of this study was to analyze the recent changes in pharmacovigilance in the EAEU countries in order to adopt the strategy of the pharmaceutical industry players.Materials and methods. The regulatory base of pharmacovigilance in the EAEU countries and the unified EAEU provisions on adverse reactions (ADR) were analyzed. A critical analysis of the current periodic safety update reports (PSUR) and risk management plans (RMP) was also carried out.Results. The united EAEU drug market is a complex system that incorporates 35 regulations, including the variety of good practice guidelines regarding the circulation of medicinal products (GMP, GCP, GLP, GDP, and GVP). This group of regulations contains basic documents on the inspection of production lines, the assessment of generic equivalence, the development of biological drugs, and the pharmacovigilance (PV). Currently, the ADR reporting in the EAEU countries is at a level lower than that in Russia. The common EAEU database of identified ADRs has been already initiated, but the number of incoming signals is quite small. The most common flaws of the PSUR are the late reports, the incorrect format and contents of those; the inconsistent information about the product, different from that of Roszdravnadzor, the discrepancy between the Patients information leaflet ("Instruction for medical use") and the Summary of Product Characteristics (SmPC), and the lack of important and relevant scientific and clinical information. In the EAEU, the submission of Risk Management Plan (RMP) as part of the registration dossier is required for any new medication (New Chemical Entity), including a new combination of drugs. The present article also covers other updates in the Pharmacovigilance system, regulated by the Good Pharmacovigilance practice, which entered into effect on 01.01.2017, as well as the updated tasks for harmonization within the EAEU.Conclusions. The medicinal products circulating in the EAEU have to be checked for their efficacy and safety in order to identify possible negative consequences and/or individual patient intolerance. This information will serve to warn the medical staff and patients, veterinary specialists and animal owners about potential hazards of using these products. In the near future, the Eurasian Union plans to launch a "sanitation" campaign in the pharmaceutical market and get rid of low-effective and unsafe drugs. In this respect, the issues of pharmacovigilance become particularly relevant.